Manajemen Tenaga Kerja pada Kegiatan Pemeliharaan Tanaman Karet di PTPN I Regional 3, Kebun Balong, Kecamatan Keling, Kabupaten Jepara - Nugroho, Febri Aldwin; Sayekti, Agatha Ayiek Sih; Puruhito, Dimas Deworo (AGRIFITIA : Journal of Agribusiness Plantation, 2025)
Rubber (Hevea brasiliensis) is one of the important agricultural commodities for Indonesia and the international scope. In Indonesia, rubber is one of the agricultural products that supports the country's economy. Rubber production in Indonesia needs to be greatly increased because judging from the land area owned by Indonesia is superior to other countries, so that Indonesia can rank at the top for rubber producers (Indarto, 2017). This study aims to examine the implementation of labor management for rubber plant maintenance in PTPN 1 Regional 3 Kebun Balong. This research was conducted at PTPN 1 Regional 3 Kebun Balong, in June-July 2024. The research method used is a descriptive method with a qualitative and quantitative approach. The sample was determined using the purposive sampling method, with the number of respondents being 1 Assistant, 1 Foreman and 28 rubber plant maintenance employees. The results of the study explain that labor management in PTPN I Regional 3 has been running well, which can be seen from labor procurement, labor development, labor compensation, division of types of work, labor maintenance, labor discipline, and labor dismissal, this is in accordance with the function of human resource management.